Figures of speech used in the Bible explained and illustrated - Bullinger, Ethelbert W. 1837-1913 (Grand Rapids, MI Baker, 1898)
Includes bibliographical references and indexes.
23rd reprint, 2003.
Keywords: Bible -- language, style